2014
DOI: 10.1016/j.jpowsour.2014.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Na[FSA]-[C3C1pyrr][FSA] ionic liquids as electrolytes for sodium secondary batteries: Effects of Na ion concentration and operation temperature

Abstract: As electrolytes for sodium secondary batteries operating over a wide temperature range, Na[FSA]-[C 3 C 1 pyrr][FSA] (FSA = bis(fluorosulfonyl)amide, C 3 C 1 pyrr = N-methyl-Npropylpyrrolidinium) ionic liquids have been investigated. The effects of Na ion concentration (0-60 mol% Na[FSA]) and operation temperature (253-363 K) on the viscosity and ioncic conductivity and charge-discharge performance of Na/Na[FSA]-[C 3 C 1 pyrr][FSA]/NaCrO 2 cells are studied. Results show that Na ion concentration strongly affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
112
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 32 publications
6
112
1
Order By: Relevance
“…11,14 In addition to this, Nohira and Hagiwara et al have reported that Py13-FSA is useful for NaCrO 2 cathode. 15 These results indicate that Py13-FSA can improve the performance because it probably forms thin and uniform surface layer to allow uniform sodiation/ desodiation reactions on the electrode.…”
Section: Resultsmentioning
confidence: 82%
“…11,14 In addition to this, Nohira and Hagiwara et al have reported that Py13-FSA is useful for NaCrO 2 cathode. 15 These results indicate that Py13-FSA can improve the performance because it probably forms thin and uniform surface layer to allow uniform sodiation/ desodiation reactions on the electrode.…”
Section: Resultsmentioning
confidence: 82%
“…A Na/NaCrO 2 half-cell has been shown to exhibit a high reversible capacity of about 120 mAh (g-NaCrO 2 ) -1 between 2.5 and 3.5 V at 90 ÂșC. [37] Fig. 6 shows the charge-discharge curves of an HC/NaCrO 2 full cell between 1.5 and 3.5 V at 90 ÂșC.…”
Section: Resultsmentioning
confidence: 99%
“…Na-ion, Mg-ion and metal-air batteries) for the development of potentially safer devices. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Furthermore, the high (electro)chemical stabilities and non-volatilities exhibited by many IL structures provides interesting electrolyte media for electrochemical gas sensors (e.g. for O 2 , [16][17][18][19] CO 2 ,20,21 NO 2 22 ) where traditional solvents are prone to evaporation leading to device failure, and also for electromechanical actuator, [23][24][25] and electrodeposition applications.…”
mentioning
confidence: 99%